The World Needs Who You Were Made to Be - Gaines, Joanna 1978-; Swaney, Julianna (Nashville, TN : Tommy Nelson, 2020)
"Author Joanna Gaines follows up her #1 New York Times bestselling We Are the Gardeners with The World Needs Who You Were Made to Be. This children's book, beautifully illustrated by Julianna Swaney, celebrates how creativity and acceptance can come together in a bright and beautiful adventure"--
Keywords: Self-acceptance -- Juvenile literature; Individual differences -- Juvenile literature; Self-acceptance -- Juvenile literature; Individual differences -- Juvenile literature; Picture books